Olimpíada brasileira de matemática das escolas públicas: desafios enfrentados por professores e alunos da rede pública municipal no município de assú-rn - Souza, Janio Luiz de Aquino de (Universidade Federal Rural do Semi-Árido, 2018)
The aim of the current study is to discuss the challenges of teachers and students from the municipal schools of the town of Assú-RN, faced during the preparation process to the Brazilian Mathematics Olympiad of Public Schools exams (OBMEP). The research approach is qualitative, of an explanatory nature, and it worked with the main people of the pedagogical practice, as well as a questionnaire was applied with a purpose of obtaining the necessary data to carry out the analysis. With the obtained information, some pertinent points were raised, such as the dissemination in schools, the importance of the incentive and provide stimulus to motivate teachers and students in this preparation process, as well as some suggestions with the purpose of possible provoking concerns among the subjects involved in this event. About the theorical reference, it was resorted to bibliographic research, as well as documentary research on OBMEP's officials websites, with a view to analyzing the problem and pointing out possible solutions to the obstacles that permeate the subject under discussion. The research results indicate the meaning that this competition has to improve students' learning and interest in Mathematics, allowing a reflection on the challenges and the identification of mechanisms to overcome the difficulties reported
Keywords: Olimpíadas; Matemática; Escolas públicas; Aprendizagem; Olympiads; Mathematics; Public schools; Learning; CIENCIAS EXATAS E DA TERRA::MATEMATICA